2013
DOI: 10.1055/s-0033-1353214
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tai-Chi for Decreasing Acute Pain in Fibromyalgia Patients

Abstract: Tai-Chi has shown benefits in physical and psychological outcomes in diverse populations. We aimed to determine the changes elicited by a Tai-Chi program (12 and 24 weeks) in acute pain (before vs. after session) in fibromyalgia patients. We also assessed the cumulative changes in pain brought about by a Tai-Chi program. Thirty-six patients (29 women) with fibromyalgia participated in a low-moderate intensity Tai-Chi program for 12 weeks (3 sessions/week). Twenty-eight patients (27 women) continued the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…The effect of diverse exercise interventions in fibromyalgia pain improvements is well documented (Segura‐Jiménez et al., , ; Rahman et al., ). The scientific literature shows that conventional exercise interventions and complementary and alternative exercise programs lead to pain improvements in this population (Carbonell‐Baeza et al., ; Segura‐Jiménez et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of diverse exercise interventions in fibromyalgia pain improvements is well documented (Segura‐Jiménez et al., , ; Rahman et al., ). The scientific literature shows that conventional exercise interventions and complementary and alternative exercise programs lead to pain improvements in this population (Carbonell‐Baeza et al., ; Segura‐Jiménez et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of diverse exercise interventions in fibromyalgia pain improvements is well documented (Segura‐Jiménez et al., , ; Rahman et al., ). The scientific literature shows that conventional exercise interventions and complementary and alternative exercise programs lead to pain improvements in this population (Carbonell‐Baeza et al., ; Segura‐Jiménez et al., , ). Despite the controversial low clinical relevance of these improvements, a recent study observed that exercise therapy might be even better than pharmacological interventions as a fibromyalgia treatment (Rahman et al., ), which highlights the strong link that seems to exist between fibromyalgia pain and physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Seemingly supervised Tai Chi can reduce symptoms in patients with FM. 7,[9][10][11][12] However, research is limited into the mechanism behind these positive outcomes. Wong…”
Section: Mechanisms Of Tai Chimentioning
confidence: 99%
“…Tai chi is a Chinese martial art based on slow, continuous movements coordinated with breathing to enable meditation with movement that seeks to balance internal energy, or qi, and mediate physical and psychologic well‐being. Low‐quality evidence supports the benefit of Tai Chi on tension headaches, LBP, fibromyalgia, and arthritis [40‐45], with the conditional recommendation from the American College of Rheumatology for patients with knee OA to participate in tai chi programs [46].…”
Section: Pt and Modalitiesmentioning
confidence: 99%